2021
DOI: 10.1111/maps.13732
|View full text |Cite
|
Sign up to set email alerts
|

Solar energetic particle tracks in lunar samples: A transmission electron microscope calibration and implications for lunar space weathering

Abstract: Transmission electron microscope (TEM) imaging techniques combined with focused ion beam sample preparation were used to calibrate the solar energetic particle track production rate in lunar samples. Track density measurements by TEM as a function of depth were obtained from lunar rock 64455 that has a well‐constrained exposure age of 2 Myr giving a track production rate of 4.4 ± 0.4 × 104 tracks cm−2 yr−1 for a 2π exposure at 1 AU. The typical space weathering effects in mature lunar soils (both vapor‐deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 64 publications
4
52
0
Order By: Relevance
“…The same texture has been observed in olivine (Keller et al., 2021). The retaining of crystal structures is related to the radiation resistance of different minerals (Burgess & Stroud, 2018; Keller et al., 2021; Wirth, 2007), or the ion damage could be rapidly annealed by diurnal heating on the lunar surface. Unlike silicates, phosphate and ilmenite, the iron sulfide was found to have a unique jagged surface, with no obvious solar wind‐damaged zone.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The same texture has been observed in olivine (Keller et al., 2021). The retaining of crystal structures is related to the radiation resistance of different minerals (Burgess & Stroud, 2018; Keller et al., 2021; Wirth, 2007), or the ion damage could be rapidly annealed by diurnal heating on the lunar surface. Unlike silicates, phosphate and ilmenite, the iron sulfide was found to have a unique jagged surface, with no obvious solar wind‐damaged zone.…”
Section: Resultssupporting
confidence: 80%
“…The amorphized zone (∼50 nm in thickness) retains the same parallel lamella texture with the identical compositions of the underlying host pyroxenes in STEM‐HAADF images (Figure 2b; Figure S2 in Supporting Information ), providing robust evidence that solar wind irradiation, instead of micrometeorite impacts, created it. This clast has an exposure age of ∼3.2 × 10 5 years (Figure S8 in Supporting Information ), estimated from the solar flare track density in pyroxene based on a 2π track production rate of 4.4 ± 0.4 × 10 4 tracks cm −2 yr −1 at 1 AU (Keller et al., 2021). Ilmenite and merrillite have significantly thicker solar wind‐damaged zones, ∼80 nm (Figure 2e) and ∼160 nm (Figure 3b), respectively, but the HRTEM images of them show lattice fringes extending to the topmost surface.…”
Section: Resultsmentioning
confidence: 99%
“…2g, h ). The differences in the degree of amorphousness among different mineral types indicate that the compact crystal structure of olivine allows it to resist the destructive effects of solar wind particles, while plagioclase is vulnerable to damage by solar wind 28 . Nanophase Fe metal (npFe 0 ) grains are dispersed as inclusions in the damaged rims of Fe-rich pyroxene and olivine.…”
Section: Resultsmentioning
confidence: 99%
“…The radiation tracks produced by the solar energetic particles (SEPs) can penetrate lunar soils at millimeter depths and leave tracks in the crystals. Although impact gardening on the lunar surface would cause the grains to be buried and still receive radiation from SEPs, previous studies have shown that the rate of track accumulation attenuates strongly when grain is buried at any depth, which indicates a low accumulation of radiation tracks after the grains are buried 28 . A positive correlation between water content and track density can be observed in these grains, suggesting that the track density can be used to reflect the exposure time when the grains receive solar wind implantation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation